Foster care as a child protection measure in Malaysia: a literature review - A. Kadir, Nadhilah; Mohd, Azizah (SecholianPublication., 2022)
Foster care has been practised widely in other countries as one of the alternative care options for children in need of care and protection. In general, foster care refers to a placement of a child either temporarily or permanently, in the care of a person other than a parent. However, at present, there is no specific legislation governing foster care in Malaysia, except for the limited provisions in the Child Act 2001. A review of foster care as a child protection measure in Malaysia from a legal perspective was conducted and four themes emerged, namely, (a) concept of foster care; (b)international legal framework for foster care; (c) foster care in other countries; and (d) foster care in Malaysia. Results indicate that there is a comprehensive literature on foster care from a legal perspective but small literature in the context of Malaysia since there is no specific legislation governing it. At present, foster care is administered based on the practice of the Malaysia Social Welfare Department.